2017
DOI: 10.1111/ejn.13529
|View full text |Cite
|
Sign up to set email alerts
|

Dorsomedial prefrontal cortex and cerebellar contribution to in‐group attitudes: a transcranial magnetic stimulation study

Abstract: We tend to express more positive judgments and behaviors toward individuals belonging to our own group compared to other (out-) groups. In this study, we assessed the role of the cerebellum and of the dorsomedial prefrontal cortex (dmPFC) - two regions critically implicated in social cognition processes - in mediating implicit valenced attitudes toward in-group and out-group individuals. To this aim, we used transcranial magnetic stimulation (TMS) in combination with a standard attitude priming task, in which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 107 publications
(135 reference statements)
1
27
0
Order By: Relevance
“…Functional connectivity analyses on social cognition confirmed task-related connectivity between the anterior CB and activation in mirror cortical areas, while the posterior CB (mainly Crus I) showed task-related connectivity with cortical areas involved in mentalizing [99,100]. Further, a recent repetitive transcranial magnetic stimulation (rTMS) study found that CB rTMS interfered with implicit social biases [101].…”
Section: Cerebellum and Cognition: Evidence From Neuroimagingmentioning
confidence: 74%
“…Functional connectivity analyses on social cognition confirmed task-related connectivity between the anterior CB and activation in mirror cortical areas, while the posterior CB (mainly Crus I) showed task-related connectivity with cortical areas involved in mentalizing [99,100]. Further, a recent repetitive transcranial magnetic stimulation (rTMS) study found that CB rTMS interfered with implicit social biases [101].…”
Section: Cerebellum and Cognition: Evidence From Neuroimagingmentioning
confidence: 74%
“…We are aware of one study which used TMS to investigate the mediating role of the cerebellum in advanced social functioning without explicit sequencing, more specifically implicit intergroup bias [ 308 ]. In this study, participants evaluated trait adjectives that were primed by a picture of an in- or outgroup member, while triple-pulse TMS (20 Hz) was delivered over the right cerebellum between prime and target.…”
Section: Cerebellar Neurostimulationmentioning
confidence: 99%
“…Taken together, research investigating the effects of cerebellar TMS on advanced social functioning is still at its infancy. Although we hypothesize that building internal models of social action sequences is the main role of the posterior cerebellum, brain stimulation can modulate advanced social processes also without explicitly targeting this sequencing function (e.g., [ 308 ]). Further research using brain stimulation to modulate the working of the cerebellum in all types of social processing might lead to novel diagnostic tools or clinical treatment methods.…”
Section: Cerebellar Neurostimulationmentioning
confidence: 99%
“…The desirability bias for the cold out-groups, on the other hand, would be associated with the brain activity in a network of regions associated with stereotypical thinking (H3), e.g. the TPJ [45][46][47][48] , ATL [49][50][51] , dmFC 52,53 , and, possibly, the IFC 54 .…”
Section: Hypothesesmentioning
confidence: 99%